2022
DOI: 10.1101/2022.01.05.475095
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure-based identification of naphthoquinones and derivatives as novel inhibitors of main protease Mpro and papain-like protease PLpro of SARS-CoV-2

Abstract: The worldwide COVID-19 pandemic caused by the coronavirus SARS-CoV-2 urgently demands novel direct antiviral treatments. The main protease (Mpro) and papain-like protease (PLpro) are attractive drug targets among coronaviruses due to their essential role in processing the polyproteins translated from the viral RNA. In the present work, we virtually screened 688 naphthoquinoidal compounds and derivatives against Mpro of SARS-CoV-2. Twenty-four derivatives were selected and evaluated in biochemical assays agains… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 162 publications
0
13
0
Order By: Relevance
“…Through virtual screening of a library of naphthoquinoidal compounds followed by enzymatic assay validation, Santos et al identified three compounds, 38 , 39 , and 40 , as potent SARS-CoV-2 PL pro inhibitors, with IC 50 values of 1.7, 2.2, and 3.1 μM, respectively ( Table 1 ). 84 Among the three hits, compound 40 had moderate inhibition against M pro , with an IC 50 of 66 μM; therefore, it was considered as a dual inhibitor for further optimization. Molecular dynamics (MD) simulations predicted that compound 39 binds non-covalently to the S3 and S4 subsites in PL pro .…”
Section: Sars-cov-2 Pl Pro Inhibitorsmentioning
confidence: 99%
“…Through virtual screening of a library of naphthoquinoidal compounds followed by enzymatic assay validation, Santos et al identified three compounds, 38 , 39 , and 40 , as potent SARS-CoV-2 PL pro inhibitors, with IC 50 values of 1.7, 2.2, and 3.1 μM, respectively ( Table 1 ). 84 Among the three hits, compound 40 had moderate inhibition against M pro , with an IC 50 of 66 μM; therefore, it was considered as a dual inhibitor for further optimization. Molecular dynamics (MD) simulations predicted that compound 39 binds non-covalently to the S3 and S4 subsites in PL pro .…”
Section: Sars-cov-2 Pl Pro Inhibitorsmentioning
confidence: 99%
“…Further studies suggested that compound 382 was a reversible SARS-CoV-2 3CL pro inhibitor, while compound 415 might form a covalent bond with Cys145 of 3CL pro . 232 Similarly, aloesin was identified as a SARS-CoV-2 3CL pro inhibitor from a fluorescence resonance energy transfer (FRET)-based THS assessment. 233…”
Section: Quinones and Their Derivativesmentioning
confidence: 99%
“…Recently, four compounds were screened to inhibit SARS‐CoV‐2 3CL pro from a compound library, with IC 50 values ranging from 0.41 to 66 μM. Further studies suggested that compound 382 was a reversible SARS‐CoV‐2 3CL pro inhibitor, while compound 415 might form a covalent bond with Cys145 of 3CL pro 232 . Similarly, aloesin was identified as a SARS‐CoV‐2 3CL pro inhibitor from a fluorescence resonance energy transfer (FRET)‐based THS assessment 233 …”
Section: Naturally Derived Sars‐cov‐2 3clpro Inhibitorsmentioning
confidence: 99%
“…Most published PLpro inhibitors are analogues of GRL-0617, a non-covalent binder identified during the previous SARS-CoV-1 outbreak . This ligand does not interact with the catalytic triad in S1 but rather binds to S3 and S4 subsites and causes conformational changes in the BL2 loop (which wraps over the inhibitor), hindering the active site’s accessibility …”
Section: Introductionmentioning
confidence: 99%
“…Recent success of virtual screening (VS) campaigns with SARS-CoV-2 Main protease (Mpro) , stimulated similar studies with PLpro. Thus, in a work by Kronenberger et al, authors identified 688 quinonoid derivatives as potential PLpro binders, from which three compounds demonstrated effective inhibition of enzymatic activity with IC 50 values in a low micromolar range. Unfortunately, these chemicals also exhibited significant cytotoxicity, but their discovery supported the deployment of large-scale VS against the PLpro catalytic triad in the active site.…”
Section: Introductionmentioning
confidence: 99%